MARKETING MIX LYSIS TOWARDS SALES OF DURIAN SOFT AT RIAU SPECIAL HOUSEHOLDS "YOLANDA" PEKANBARU - Sri Widianti (Jurnal Ekonomi, 2021)
This research was conducted at a typical souvenir shop from Riau "Yolanda" Pekanbaru which is located in the tourist market or the market under Jalan M. Yatim Pekanbaru. The purpose of this study was to determine how much influence the marketing mix has on sales of durian lempuk and what policies are taken by the company to increase sales of durian lempuk. The sampling method used accidental sampling, which is a sampling technique based on chance, namely anyone who happens to meet the researcher and meets the requirements to be used as a sample. The sample used in this study amounted to 71 people. Data analysis in this research is quantitative analysis using multiple linear regression method and the data is analyzed using SPSS 17.00 program.The results of hypothesis testing show that the calculated F value is 13.105 > F table is 2.35, then the hypothesis is accepted. Then the regression model shows that simultaneously product, price, promotion and distribution affect consumers to the sale of durian lempuk at the typical Riau souvenir outlet "Yolanda. The value of R Square is 0.443, which means 44.3% of products, prices, promotions and distributions affect consumers towards the sale of durian lempuk at typical Riau souvenir shops, while the rest (100% -44.3% = 55.7%) is influenced by -other reasons not investigated in this study.